Khảo sát mức độ biến dạng tinh thể bề mặt mòn va đập xoay bằng phương pháp nhiễu xạ Rongen - Nguyễn, Anh Tuấn (Bộ Giáo dục, 2013)
Survey on the changes of parameters of crystal network under the mechanical pressure by Rongen diffract method. Have researched and compared the crystal deformation between wearing out sufferred sample with the standards ample by the changes of 3 factors: + Collision energy + Rotation speed + Material hardness The article has estimated not only the separated in fluence of each factor but also the simultanously effect of them by the second degree orthgonal experiment Design. The results of study; are obtained by computer according to above mentioned mathematical methods. Base on the study results, the article has given some conclusions as following: + By Ronge diffract method, it is possible to measure the crystal deformation degree of collision and rotation wearing - out surface. The harder material is, the more crystal deformation degree it has. The softer material has smaller crystal deformation degree. + Collision energy is the main factor influences to the crystal network deformation on the wearing out surface. Rotation speed has minor influence in case the material hardness is high and has unnoticeable influence in case of soft material.